Assessment of Pre-Primary II Teachers’ Resource Development and Utilization Skills for CBC Implementation in Language Activities - Adongo, Jane Akinyi; Opiyo, Rose A; Ouda, James Bill (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Kenya's educational landscape has witnessed a transformative shift towards curriculum reform, aiming to enhance the quality of education. A central element of this reform has been the transition from mere knowledge and skill acquisition to fostering the creation and practical application of knowledge and skills. This study specifically focused on evaluating the readiness of teachers to implement the Competence-Based Curriculum (CBC) in language activities for Pre-Primary II students within Nambale Sub County, Kenya. The research objective was to assess Pre-Primary II teachers' ability to develop and utilize learning resources as an essential component of implementing CBC for language activities. Vygotsky's socio-cultural theory served as the theoretical framework underpinning this study. Mixed convergent research design was employed, including a sample size that involved 20 Head Teachers, 20 teachers-in-charge, 40 Early Childhood Development Education (ECDE) teachers, the County Director ECDE, the Sub County Quality Assurance and Standards Officer (QASO) and the Sub County Director of Education (MOE). These individuals were purposively chosen due to their intimate involvement with educational processes. Data collection methods incorporated questionnaires, interviews, classroom observations, and document analysis. The analysis of the study's findings revealed a significant relationship between the teachers' ability to develop and utilize resources and the effective implementation of CBC in language activities. This relationship is underscored by a coefficient value (R) of 0.619 and an R square value of 0.383 at P=0.000, signifying that 38.3% of the variation in the implementation of CBC language activities is explained by the teachers' capacity to develop and utilize resources. The study recommends the enhancement of the successful implementation of CBC in language activities for Pre-Primary II learners, such as early teacher preparation, support for resource development and acquisition, structured planning of learning experiences, and capacity-building of teacher’s initiatives.